Application of The Ultimum Remedium Principle in Tax Criminal Actions: A Juridical Study - Hendri Hendri (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This research aims to analyze the application of the ultimum remedium principle in tax criminal actions in Indonesia. The ultimum remedium principle is a legal principle that states that criminal punishment is the last resort in law enforcement. This principle is relevant in the context of tax offenses because the main purpose of tax law is to increase tax compliance and collect state revenue, not to punish taxpayers. This research employs a normative research method with a doctrinal legal approach. Research data is obtained from a study of literature and regulations related to tax offenses. The research findings indicate that the ultimum remedium principle has been implemented in Indonesian tax criminal law. This is evident from the provisions regulating administrative sanctions and criminal tax sanctions. Administrative sanctions are lighter than criminal sanctions and must be applied first before criminal sanctions can be imposed. This research also shows that several factors can influence the application of the ultimum remedium principle in tax offenses. These factors include the seriousness of the tax offense, the taxpayer's malicious intent, and the deterrent effect that is desired.